2000
DOI: 10.2136/sssaj2000.643949x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Calcium and Phosphate Release from Hydroxy‐Apatite by Mycorrhizal Hyphae

Abstract: The role of vesicular‐arbuscular mycorrhiza (VAM) in facilitating the uptake of sparingly soluble nutrients from the soil has been well documented. Uncertainty remains regarding the mechanism controlling the dissolution of tightly bound P such as in phosphate rock. We studied the differential Ca and P uptake by the external mycelium of VAM in maize (Zea mays L.) grown in an acid tropical soil supplied with hydroxy‐apatite (HA). Three experiments were conducted in modified double‐pot systems where Ca was adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Targeted attacks on minerals have been previously reported for mycorrhizal fungi (Ness and Vlek, 2000;Bonneville et al, 2009). Hallmarks of a mycorrhizal attack on apatite include removal of P from soil solution via uptake, with concomitant increase in Ca 2+ near the dissolving apatite crystal (Ness and Vlek, 2000).…”
Section: Apatite Dissolution and Fate Of Phosphorousmentioning
confidence: 86%
See 1 more Smart Citation
“…Targeted attacks on minerals have been previously reported for mycorrhizal fungi (Ness and Vlek, 2000;Bonneville et al, 2009). Hallmarks of a mycorrhizal attack on apatite include removal of P from soil solution via uptake, with concomitant increase in Ca 2+ near the dissolving apatite crystal (Ness and Vlek, 2000).…”
Section: Apatite Dissolution and Fate Of Phosphorousmentioning
confidence: 86%
“…Hallmarks of a mycorrhizal attack on apatite include removal of P from soil solution via uptake, with concomitant increase in Ca 2+ near the dissolving apatite crystal (Ness and Vlek, 2000). Argillans are a very prominent component of the soil fabric just above the last appearance of apatite.…”
Section: Apatite Dissolution and Fate Of Phosphorousmentioning
confidence: 99%
“…Biofertilizing PGPR sometimes enhances plant growth indirectly by stimulating the relationship between the host plant and beneficial rhizospheric fungi such as arbuscular mycorrhizae (AM). Although AM by themselves are well known to enhance the uptake of various soil nutrients (especially P) (Marschener, 1998;Ness and Vlek, 2000). Studies showed that their coinoculation with some PGPR could enhance the relationship between plant and fungal symbionts.…”
Section: Stimulation Of Plant Fungal Symbiosismentioning
confidence: 99%
“…Most agricultural crops are potential host plants for arbuscular mycorrhizal (AM) fungi. In addition to an exudation of carboxylates, phosphatases and plant hormones, mycorrhiza increase the exploitation of the soil volume by the hyphal network, which increases the active adsorption surface and spreads beyond the phosphate depletion zone (Lange Ness and Vlek 2000;Martin et al 2001). Mycorrhizal hyphae have a higher affinity for phosphate as expressed in the Michaelis-Menten equation by a lower Km value and absorb P at lower solution concentrations than roots do (Lange Ness and Vlek 2000).…”
Section: Interactions Between Microorganisms and Higher Plants From Cmentioning
confidence: 99%
“…In addition to an exudation of carboxylates, phosphatases and plant hormones, mycorrhiza increase the exploitation of the soil volume by the hyphal network, which increases the active adsorption surface and spreads beyond the phosphate depletion zone (Lange Ness and Vlek 2000;Martin et al 2001). Mycorrhizal hyphae have a higher affinity for phosphate as expressed in the Michaelis-Menten equation by a lower Km value and absorb P at lower solution concentrations than roots do (Lange Ness and Vlek 2000). AM fungi store phosphate in the form of orthophosphate, polyphosphate and organic P in their vacuoles and transfer it to the roots of the host plant (Ezawa et al 2002).…”
Section: Interactions Between Microorganisms and Higher Plants From Cmentioning
confidence: 99%